2012
DOI: 10.1155/2012/651630
|View full text |Cite
|
Sign up to set email alerts
|

Selenium in the Prevention of Anthracycline-Induced Cardiac Toxicity in Children with Cancer

Abstract: High cumulative doses of anthracyclines (300–500 mg/m2) used in the treatment of children with cancer may result in cardiotoxicity, a major long-term adverse effect that limits clinical usefulness of this class of chemotherapeutic agents. We assessed anthracycline-induced cardiotoxicity by measuring Pro-BNP levels and echocardiographic (ECHO) findings and investigated potential protective effect of selenium (Se) supplementation in a group of pediatric cancer patients. Plasma level of Pro-BNP was measured, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Most of the studies have been done in experimental animal models. For example, N-acetylcysteine and selenium (Se) did not significantly reduce the activity of xanthine oxidase (XOD) in a mouse model [ 77 ], although, according to a small clinical study in nine children with a high pro-BNP level and/or cardiac failure, Se supplementation proved to prevent AIC [ 78 ].…”
Section: Antioxidant Agents – Dexrazoxanementioning
confidence: 99%
“…Most of the studies have been done in experimental animal models. For example, N-acetylcysteine and selenium (Se) did not significantly reduce the activity of xanthine oxidase (XOD) in a mouse model [ 77 ], although, according to a small clinical study in nine children with a high pro-BNP level and/or cardiac failure, Se supplementation proved to prevent AIC [ 78 ].…”
Section: Antioxidant Agents – Dexrazoxanementioning
confidence: 99%
“…Selenium acts as a cofactor for the enzyme glutathione peroxidase and catalyses the reaction of hydrogen peroxide reduction by using glutathione. In children with cardiac failure and raised Pro-BNP levels, selenium has shown cardioprotective effects 30. In animal studies conducted by Walker et al , mice prophylactically managed with probucol after treatment with DOX and TRZ showed preserved systolic function.…”
Section: Discussionmentioning
confidence: 99%
“…Anjiyotensin dönüştürücü enzim (ACE) inhibitörü, anjiyotensin reseptör blokeri (ARB) veya β-bloker ajanlar tedaviye eklendiğinde kısalma fraksiyonunda ve sol ventrikül boyutlarında düzelme olmakta, ancak uzun dönemde etkileri sınırlı kalmaktadır. Radyoterapinin toksik etkisi ise "3-boyutlu", "intensity modulated", "stereotactic" ve "proton terapisi" gibi yeni geliştirilen teknikler sayesinde hem verilen doz ayarlanarak hem de uygulanan alan sınırları net olarak belirlenerek azaltılabilmektedir (2,5,(8)(9)(10)(11).…”
Section: Kardi̇yovasküler Toksi̇si̇teni̇n öNlenmesi̇unclassified